Electrochemical Monitoring of Paclitaxel‐Induced ROS Release from Mitochondria inside Single Cells - Jiang, Hong; Zhang, Xin‐Wei; Liao, Quan‐Lan; Wu, Wen‐Tao; Liu, Yan‐Ling; Huang, Wei‐Hua (Small (Weinheim an der Bergstrasse, Germany), 2019)
Mitochondria are believed to be the major source of intracellular reactive oxygen species (ROS). However, in situ, real‐time and quantitative monitoring of ROS release from mitochondria that are present in their cytosolic environment remains a great challenge. In this work, a platinized SiC@C nanowire electrode is placed into a single cell for in situ detection of ROS signals from intracellular mitochondria, and antineoplastic agent (paclitaxel) induced ROS production is successfully recorded. Further investigations indicate that complex IV (cytochrome c oxidase, COX) is the principal site for ROS generation, and significantly more ROS are generated from mitochondria in cancer cells than that from normal cells. This work provides an effective approach to directly monitor intracellular mitochondria by nanowire electrodes, and consequently obtains important physiological evidence on antineoplastic agent‐induced ROS generation, which will be of great benefit for better understanding of chemotherapy at subcellular levels. A platinized SiC@C nanowire electrode with excellent electrochemical and mechanical performance is fabricated and inserted into single cells to monitor reactive oxygen species (ROS) generation from intracellular mitochondria. This allows in situ quantification of paclitaxel‐induced ROS production in real time and identification of the site of which paclitaxel induces mitochondrial ROS generation inside single living cells.